2000
DOI: 10.1021/la000194w
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of the TiClx/MgCl2 Model Ziegler−Natta Polymerization Catalysts:  Adsorption Site Studies Using Mesitylene Thermal Desorption

Abstract: Temperature-programmed desorption (TPD) of physisorbed mesitylene molecules has been used as a nondestructive surface probe to distinguish the surface adsorption sites of model Ziegler-Natta polymerization catalysts. A MgCl2-supported titanium chloride film (TiClx/MgCl2) was fabricated on an inert gold substrate by codeposition of Mg metal and TiCl4 from the gas phase. The mesitylene TPD probe revealed two types of surface adsorption sites. The dominant site was attributed to the basal plane of these halide cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Fig. 7 displays the mesitylene TPD results for a well characterized MgCl 2 support film produced by thermal evaporation of MgCl 2 on Au (20). From structural information on the MgCl 2 film (12)(13)(14), the Ϸ200-K desorption site is attributed to the (001) basal plane structure where the chloride ions at the outermost layer are close-packed and the metal ions under the chloride layer are coordinated to six chloride ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 7 displays the mesitylene TPD results for a well characterized MgCl 2 support film produced by thermal evaporation of MgCl 2 on Au (20). From structural information on the MgCl 2 film (12)(13)(14), the Ϸ200-K desorption site is attributed to the (001) basal plane structure where the chloride ions at the outermost layer are close-packed and the metal ions under the chloride layer are coordinated to six chloride ions.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their high cross-sections in interactions with the condensed phase, these charged particles interact mostly with surface species. In the case of electrons, the surface chloride ions are removed by electron-induced desorption (20).…”
Section: Synthesis Of Heterogeneous Ziegler-natta Model Catalysts Undmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The TiCl y /MgCl 2 film grown at 300 K had the Ti oxidation state distribution similar to that of TiCl y /Au grown at 300 K. Angle-resolved XPS analysis indicated that both TiCl y films consist of a monolayer of Ti The adsorption site distribution on the model Ziegler-Natta catalyst surfaces was detected with TPD as a weakly bound probe molecule that leaves the catalyst surface chemically undisturbed. 15,20 Mesitylene was the best among the probe molecules tested in our laboratory. 15 Although this method could not distinguish the metal composition and oxidation state due to chlorine termination of the catalyst surface, it could differentiate the different adsorption sites depending on the heat of adsorption, which in turn depended on the surface chlorine structure.…”
Section: The Ticl Y Multilayer Film As a Model System For The Ticl 3 mentioning
confidence: 94%
“…In TPD of the mesitylenecovered catalyst surface, the heat of mesitylene desorption provided information about the surface structure of the model catalyst film. 15,20,21 The polymerization rate on the model catalyst was measured with LRI. This technique is based on the refractive index difference between the polymer and the catalyst.…”
Section: Surface Science Approachesmentioning
confidence: 99%